2022
DOI: 10.7577/njcie.4838
|View full text |Cite
|
Sign up to set email alerts
|

Vocational special needs teachers promoting inclusion in Finnish vocational education and training

Abstract: The role of Finnish vocational special needs teachers has changed during the last decades according to work-life needs and inclusive ambitions in education. In addition to substance competence, teachers need pedagogical knowledge and special education skills. This study investigates descriptions by Finnish vocational special needs teachers of the interaction with students who receive intensive learning support, and the study traces their opportunities to support the students in vocational colleges, work life, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Ryökkynen et al (2002) found that interaction between teachers and students in Finnish vocational education takes place primarily in teaching situations, in personal dialogues in connection with the planning of students' individual development plans, and in informal meetings between teachers and students. The importance of interaction in SNE in VET is corroborated also by Ryökkynen and Räty (2022), who point to the importance of involving the entire learning environment in order to ensure a secure and including environment where students dare to ask questions and express their needs, which is also important in their future working life. In the research field of SEN in the Swedish upper secondary school, Yngve (2020) shows that there is a clear connection between high school absence, attending a vocational upper secondary school programme or having a neuropsychiatric diagnosis and students' perceived need for support in several school subjects.…”
Section: Previous Research On Vocational Education and Special Needs ...mentioning
confidence: 89%
See 1 more Smart Citation
“…Ryökkynen et al (2002) found that interaction between teachers and students in Finnish vocational education takes place primarily in teaching situations, in personal dialogues in connection with the planning of students' individual development plans, and in informal meetings between teachers and students. The importance of interaction in SNE in VET is corroborated also by Ryökkynen and Räty (2022), who point to the importance of involving the entire learning environment in order to ensure a secure and including environment where students dare to ask questions and express their needs, which is also important in their future working life. In the research field of SEN in the Swedish upper secondary school, Yngve (2020) shows that there is a clear connection between high school absence, attending a vocational upper secondary school programme or having a neuropsychiatric diagnosis and students' perceived need for support in several school subjects.…”
Section: Previous Research On Vocational Education and Special Needs ...mentioning
confidence: 89%
“…This approach is also shown in the teachers' professional interaction with the students (cf. Ainscow, 1998Ainscow, , 2002Gidlund, 2020;Ryökkynen & Räty, 2022;Tangen, 2012) where they not only try to acquire knowledge about the students' varied needs, but also translate the knowledge into customised long-term sustainable solutions.…”
Section: The Vet Teachers' Work With Snementioning
confidence: 99%
“…The new special needs teachers’ training in Italy ( Ianes et al, 2020 ; Toto and Limone, 2021 ) has opened new scenarios of psychological, pedagogical, and methodological reflection aimed at enhancing inclinations, skills, potential and needs of each student in a lifelong learning perspective ( Ryökkynen and Räty, 2022 ; Shank and Santiague, 2022 ; McKenzie et al, 2023 ). Promoting, strengthening, and extending the accessibility of opportunities for learning to special populations are essential prerogatives and development aims for ensuring children and adolescents’ inclusion in the school setting ( Van Mieghem et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%